Religiosity and Sexual Risk Behaviors Among African American Cocaine Users in the Rural South - Montgomery, Brooke E.E. (J Rural Health, 2014)
PURPOSE: Racial and geographic disparities in human immunodeficency virus (HIV) are dramatic and drug use is a significant contributor to HIV risk. Within the rural South, African Americans who use drugs are at extremely high risk. Due to the importance of religion within African American and rural Southern communities, it can be a key element of culturally-targeted health promotion with these populations. Studies have examined religion’s relationship with sexual risk in adolescent populations, but few have examined specific religious behaviors and sexual risk behaviors among drug-using African American adults. This study examined the relationship between well-defined dimensions of religion and specific sexual behaviors among African Americans who use cocaine living in the rural southern United States. METHODS: Baseline data from a sexual risk reduction intervention for African Americans who use cocaine living in rural Arkansas (N = 205) were used to conduct bivariate and multivariate analyses examining the association between multiple sexual risk behaviors and key dimensions of religion including religious preference, private and public religious participation, religious coping, and God-based, congregation-based, and church leader-based religious support. FINDINGS: After adjusting individualized network estimator weights based on the recruitment strategy, different dimensions of religion had inverse relationships with sexual risk behavior, including church leadership support with number of unprotected vaginal/anal sexual encounter and positive religious coping with number of sexual partners and with total number of vaginal/anal sexual encounters. CONCLUSION: Results suggest that specific dimensions of religion may have protective effects on certain types of sexual behavior, which may have important research implications.